The Altered Functional Connectivity With Pain Features Integration and Interaction in Migraine Without Aura - Tian, Zilei; Yin, Tao; Xiao, Qingqing; Dong, Xiaohui; Yang, Yunhong; Wang, Menglin; Ha, Guodong; Chen, Jiyao; Liang, Fanrong; Zeng, Fang; Lan, Lei (Frontiers in Neuroscience, 2021)
Migraine without aura (MwoA) is a primary type of migraine, a common disabling disorder, and a disabling neurological condition. The headache is a complex experience, a common form of pain, in which multiple sensory information dimensions are combined to provide a unified conscious event. Migraine ictal have unique neuroimage biomarkers, but the brain is also affected during the inter-ictal phase. According to the current studies, a hypothesis was constructed that the altered integration of pain spatial and intensity information impacts headache intensity in the inter-ictal period. Methods: In this study, we applied theory-based region-to-region functional connectivity analyses to compare the differences in resting-state functional connectivity between MwoA participants and healthy controls with the pain integration hypothesis. After the correlation matrices between functional connectivity edges and clinical symptoms were constructed, the moderating effect and simple slope tests were investigated to explain whether and how the dysfunction of pain features discrimination affects the clinical symptoms. Results: Functional connectivity analyses showed significantly decreased functional connectivity edges between the left dorsolateral superior frontal gyrus and left insula, and an increased functional connectivity edge between the left dorsolateral superior frontal gyrus and bilateral angular gyrus. The correlation matrix showed no significant correlation between significantly altered FC edge and headache duration, frequency, SAS, and SDS. Only one significantly altered edge in the MwoA condition was significantly correlated with headache intensity. Moderating Module 1 and 2 manifested the moderator variable (altered rs-FC edge) moderated the link between the normal edges and headache intensity. Conclusions: The pain features integration processes in migraineurs vary from HCs, related to the clinical symptoms during a migraine attack. Moreover, the clinical symptoms will be affected by one or more discrimination modules. And the spatial or intensity discrimination modules have a higher impact when combined with another module on clinical symptoms than the single module.